Política externa brasileira de migrações - Lívia Castelo Branco Marcos Milanez (Meridiano 47, 2017)
This article discusses the change in priority in the Brazilian foreign policy given to the defense of Brazilian migrants rights; explains the motivations for the historical neglect of these rights and demonstrates that the Foreign Office has been changing the priority given to Brazilian migrations in the last two decades.